PENGARUH PENGEMBANGAN SEKTOR INDUSTRI TERHADAP PERTUMBUHAN EKONOMI DI INDONESIA : Introduction, Research Method, Research Results and Discussion, Conclusion - Diah Sagita Fitri; Rahmat Gus Faozan; Sari NurkhasanahSari Nurkhasanah; Heni Noviarita (CV. KAMPUSA AKADEMIK PUBLISHING, 2025)
The purpose of this study is to determine the impact of industrial sector development on Indonesia's economic growth, which is one of the main pillars in improving people's welfare. The research method used is qualitative descriptive analysis and data collection is carried out through a literature review of various relevant sources such as articles and statistical reports. The results show that the industrial sector makes a significant contribution to gross domestic product (GDP) and job creation, as well as contributing to increasing value creation through raw material processing. In addition, the development of the industrial sector also encourages innovation and technological progress which are very important in increasing Indonesia's competitiveness in the global market. This study highlights the importance of government policy support in creating an environment that supports the growth of the industrial sector so that it can contribute more to sustainable economic growth in Indonesia.